The Adjustments that can be Made to the Internationalization Strategy of the Chinese Internet Industry in the Face of COVID-19 - Tan, Ruiqi (2022)
The Chinese Internet industry is growing rapidly. Many Chinese Internet companies are expanding the market, improving competitiveness and finding new customers through internationalization. In recent years, China has seen an increasing number of studies on internationalization in various manufacturing sectors, but less attention has been paid to the Chinese Internet industry. In addition, the emergence of COVID-19 presents both opportunities and challenges for the internationalization of China's Internet industry. As the pandemic has occurred in the last two years, there is less research on the subject. To fill the research gap, this paper focuses on the internationalization of the Chinese Internet industry, exploring whether the internationalization strategy of the Chinese Internet industry needs to be adjusted in the current environment and how to adjust. The research questions are addressed through quantitative analysis and a case study. The conclusion is that the internationalization of the Chinese Internet industry needs to be adjusted and that can be adjusted at five levels: individual, group, company, industry and national.